Exploring the Necessity of Psychological Rounds and Psychological Interventions in General Hospitals in the Post-COVID-19 Period - Tang, PeiXi; Lee, MaoSheng (Frontiers in Psychology, 2022)
Objective To explore the necessity of psychological rounds and psychological intervention in the post-COVID-19 period in a general hospital. Methods Based on the current pandemic influence on Chinese people’s psychology, the medical experience, and environment were analyzed, and the feasibility of psychological evaluation and intervention were appraised with the psychological changes that might be brought by the medical behaviors, especially for surgical operations. Results Nowadays, the pandemic is under full control in China, although the pandemic is rampant abroad. In China, the “Normalized pandemic prevention” phase has begun. In the post-COVID-19 period, the prolonged pandemic has made numerous people pessimistic, angry, and other negative emotions. Several general hospitals are facing huge influences: under the influence of anxiety, such as “higher hospital-acquired infection rate,” the patient attendance rate is reduced, and the hospital income is sharply reduced. Doctor–patient conflicts are more likely to occur during the medical procedures, affecting the medical experience, and reducing the rate of re-visit and referral. Conclusion After analyzing a series of “endogenous” and “exogenous” factors of medical procedures in a general hospital in the post-pandemic period, it suggests that anxiety and depression caused by uncertainties in the medical procedures may be more obvious. Also, it is necessary to pay attention to the psychological status of patients and carry out psychological rounds and psychological interventions in general hospitals. The service quality can be improved, the medical experience can be ameliorated, and it can help general hospitals to turn “crisis” into “opportunity,” which also brings better development.